2010
DOI: 10.1158/1078-0432.ccr-10-0349
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Expression ofCD47andSIRPAin Bone Marrow and in Peripheral Blood Predicts Recurrence in Breast Cancer Patients

Abstract: Purpose: CD47 plays a variety of roles in intercellular signaling. Herein, we focused on the clinicopathologic significance of CD47 expression in human breast cancer. Our data suggest that the correlation between CD47 and signal regulatory protein α (SIRPA) expression may play a key role in the progression of breast cancer.Experimental Design: Quantitative real-time PCR was used to evaluate CD47 mRNA and SIRPA mRNA expression in bone marrow and in peripheral blood from 738 cases of breast cancer.Results: In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 29 publications
3
44
1
2
Order By: Relevance
“…For example, overall survival was significantly lower for DLBCL or mantle cell lymphoma patients who had elevated CD47 expression, and higher CD47 expression on tumor cells was associated with significantly poorer event-free survival in patients with CLL (7). Similar trends have been reported in other hematologic malignancies (5,6,8) and solid tumors (11,13,16,17). In addition, there is evidence to suggest that increased CD47 expression is associated with the transition from low-risk to high-risk MDS and subsequent transformation to AML (10).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…For example, overall survival was significantly lower for DLBCL or mantle cell lymphoma patients who had elevated CD47 expression, and higher CD47 expression on tumor cells was associated with significantly poorer event-free survival in patients with CLL (7). Similar trends have been reported in other hematologic malignancies (5,6,8) and solid tumors (11,13,16,17). In addition, there is evidence to suggest that increased CD47 expression is associated with the transition from low-risk to high-risk MDS and subsequent transformation to AML (10).…”
Section: Introductionsupporting
confidence: 65%
“…Similarly, elevated CD47 expression has been demonstrated on solid tumors, including bladder, brain, breast, colon, esophageal, gastric, kidney, leiomyosarcoma, liver, lung, melanoma, ovarian, pancreatic, and prostate tumors (11)(12)(13)(14)(15). CD47 has been found to be an adverse prognostic factor where high CD47 expression correlates with more aggressive disease and poorer clinical outcomes.…”
Section: Introductionmentioning
confidence: 92%
“…CD47 binds to SIRPa (46), an inhibitory receptor on macrophages and T cells (47)(48)(49) and is notably the only gene we found to be overexpressed in otherwise mostly dormant CTC. Previous studies on patients with breast cancer indicated the presence of CD47-positive CTC in the bone marrow, which may be responsible for tumor relapse (50). Other groups have shown that constitutive CD47 upregulation is a pivotal requirement for non-Hodgkin lymphoma immunotolerance and dissemination (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated possible correlations between genes that have been described in the literature as potential contributors to the development of metastases from cancer and RANK expression [3136,12,3748], using both the I-SPY1 and GSE25066 cohorts. Altogether, 44 genes that could be mapped to both datasets were identified (Supplemental Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we analyzed the gene expression of the RANK/RANKL/OPG pathway in patients enrolled in the I-SPY1 clinical trial and a pooled external neoadjuvant cohort, GSE25066 [1], and correlated this gene expression with tumor and clinical features, as well as outcomes. We also evaluated correlations between other genes that may be involved in the development of metastases and RANK [3136,12,3748]. …”
Section: Introductionmentioning
confidence: 99%